2017
DOI: 10.3892/mco.2017.1504
|View full text |Cite
|
Sign up to set email alerts
|

Meta‑analysis of diffusion‑weighted imaging for predicting locoregional failure of chemoradiotherapy in patients with head and neck squamous cell carcinoma

Abstract: Abstract. The purpose of this study was to evaluate the accuracy of diffusion-weighted imaging (DWI) for predicting locoregional failure of chemoradiotherapy in patients with head and neck squamous cell carcinoma (HNSCC). A comprehensive search was conducted through the EMBASE, PubMed and Cochrane Library databases for relevant publications. Stata software was used to calculate the pooled sensitivity, specificity, likelihood ratios and diagnostic odds ratios, and to construct a summary receiver operating chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Several previous studies evaluated the utility of DWI in differentiating posttreatment changes from recurrence and concluded that DWI showed high diagnostic performance. 7,11,[13][14][15][16] Morphologic imaging features for LTR described in previous literature included infiltrative mass appearance, with intermediate to high SI in T2 WIs and postcontrast enhancement. However, these features could overlap with those of benign posttreatment findings such as posttherapy inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies evaluated the utility of DWI in differentiating posttreatment changes from recurrence and concluded that DWI showed high diagnostic performance. 7,11,[13][14][15][16] Morphologic imaging features for LTR described in previous literature included infiltrative mass appearance, with intermediate to high SI in T2 WIs and postcontrast enhancement. However, these features could overlap with those of benign posttreatment findings such as posttherapy inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The other three studies were done by King et al [5] Matoba et al [15], and Vandecaveye et al [23] who assessed the correlation between locoregional outcome and ADC values as well as tumor volume measurements in primary tumors and metastatic nodes before and 3 weeks after start of treatment, they found that the intratreatment percentage change of ADC was significant predictor for locoregional control with optimal thresholds of ≥ 15.5%, 24%, and 25% to predict locoregional control after CRT respectively. A meta-analysis was performed including nine studies assessing the role of DWI (before and early during treatment) in predicting therapeutic response of HNSCC to CRT, they found that DWI had good predictive accuracy (AUC = 0.84) for locoregional failure with the optimum cut-off values for pretreatment ADC ranging from 0.86 to 1.11 × 10 −3 mm 2 /s and from 14 to 52.7% for early intratreatment percentage change in ADC [25].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of clinical studies have focused on the potential of pretreatment imaging to predict outcomes [8,9], but also early changes in qMRI metrics have been promoted as potentially predictive for treatment outcome [10,11]. Pretreatment measurements are mostly done on diagnostic MR systems or MR simulation scanners used in radiation oncology.…”
Section: Potential Applications Of Qibs In Radiotherapymentioning
confidence: 99%
“…Currently, most evidence is available for outcome prediction and response assessment to therapy. Although meta-analysis studies have been performed [8,13,14], the clinical validation of potential QIBs remains in its infancy. Establishing the link between qMRI metrics and clinical outcome, such as overall survival and disease-free survival, is very time consuming.…”
Section: Clinical Validationmentioning
confidence: 99%